Experimental and theoretical study on the propagation characteristics of stress wave in filled jointed rock mass. - Shuailong Jia; Zhiliang Wang; Jianguo Wang; Zhitang Lu; Haochen Wang (PLoS ONE)
This study is to theoretically and experimentally investigate the propagation of stress waves in the filled joint set. The time-domain recursive method is used to derive the propagation equations in the filled joint set, and the filled joints are further simplified into structural planes without joint thickness. The split-Hopkinson rock bar is modified to simulate P wave propagation normally across the parallel filled joints. The relationship among stress-closure curve, joint specific stiffness, transmission coefficient and loading rate is analyzed. The results show that, for the rock mass with a single joint, both the joint specific stiffness and transmission coefficient of different filling materials increase with loading rate. More serious particle breakage of the filling materials leads to lower joint specific stiffness and transmission coefficient. For the rock mass with two joints, the joint specific stiffness of each joint affects the transmission coefficient of the filled joint set. It is found that our theoretical calculations are basically consistent with the experimental ones, and the joint specific stiffness can well characterize the propagation behavior of stress wave in the filled parallel rock joints.